Learning how to learn from failures: The Fukushima nuclear disaster. (January 2015) - Labib, Ashraf; Harris, M.J.
Highlights: Fukushima nuclear disaster was investigated to identify root causes of the accident. FTA, RBD models used to analyse the various causes of failure. The AHP method is used to select decisions for choice of energy. Abstract: Analysis of the Fukushima nuclear reactor disaster will show how to learn from failures using multi-models. This type of analysis can enrich the modelling of causal factors, provide insight into policy making and support decisions for resource allocations to prevent such disasters. The analysis presented here is based on a workshop on learning from failures in which participants were first given a brief about the related theory, then an introduction to the analytical techniques that can be used such as FTA, and RBD. They were then given a brief in the form of a narrative of the accident derived from investigation reports and divided into small groups tasked to analyse the disaster and to present their recommendations both orally and in a written report. All the participants were asked to follow a certain presentation format. Firstly there would be a technical account of the sequence of events that would be based on research of greater depth than provided in the initial summary, one related more to the scope of their analysis. This would be followed by a review of the consequences of the accident, a presentation of their multi-model analysis of the event and a summary of generic lessons and recommendations to prevent future failures of such systems. Finally, collective feedback, focused on the generic lessons gained, was offered.